RANCANG BANGUN SISTEM INFORMASI PENGGAJIAN KARYAWAN PADA PT. LINTAS VIRTUAL GLOBALINDO BEKASI - Riyanto, Yuliadi; Dewi, Tri Kartika (JURNAL LENTERA ICT, 2018)
Abstract This research is entitled "Designing an Employee Payroll Information System at PT Lintas Virtual Globalindo Bekasi". The purpose of this study was to find out how the employee recitation information system, and the constraints faced in the information system and provide solutions to the employee payroll information system problems. Employee payroll procedures are used at PT. The Virtual Globalindo crossing in Bekasi is currently using the conventional method, namely by recording the books and assisted with Microsoft Office Excel, so that the employee payroll process runs ineffective and inefficient. Of these problems raises the idea of creating a web-based information system, in which can manage computerized employee payroll. The research method used is Library Research and Field Research. There are three actors / users in this information system, namely Employees, Admin and Finance. Employees can only access the attendance page. Then the admin can access and manage employee attendance. employee data, employee divisions, employee positions and data users, and Finance can access overtime data, salary transactions, attendance reports, salary and paycheck reports, with the Employee Payroll Information System for the Finance section, which is expected to facilitate the employee payroll process.Keywords: Design, System, Payroll.